2006
DOI: 10.1002/14651858.cd004515.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Valerian for anxiety disorders

Abstract: Since only one small study is currently available, there is insufficient evidence to draw any conclusions about the efficacy or safety of valerian compared with placebo or diazepam for anxiety disorders. RCTs involving larger samples and comparing valerian with placebo or other interventions used to treat of anxiety disorders, such as antidepressants, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 18 publications
1
38
1
Order By: Relevance
“…Although little research on alternative therapy was conducted in the past, several recent studies have reported their efficacy in patients with posttraumatic stress disorder (PTSD) [1], general anxiety disorders (GAD) through herbal therapy [2], anxiety and mood disorders through several complementary therapies [3], anxiety disorders through yoga therapy [4], and anxiety disorders through meditation and relaxation [5]. …”
Section: Resultsmentioning
confidence: 99%
“…Although little research on alternative therapy was conducted in the past, several recent studies have reported their efficacy in patients with posttraumatic stress disorder (PTSD) [1], general anxiety disorders (GAD) through herbal therapy [2], anxiety and mood disorders through several complementary therapies [3], anxiety disorders through yoga therapy [4], and anxiety disorders through meditation and relaxation [5]. …”
Section: Resultsmentioning
confidence: 99%
“…Cochrane meta-analyses found two studies of passiflora (passion flower) indicating it was as effective as benzodiazepines (Level 2) [633], and one study of valerian which found no significant differences between placebo, valerian, or diazepam (Level 2, negative) [634,635]. Unfortunately, because these preparations are poorly standardized and have substantial variation in proportion of the active ingredient in different products, they cannot be widely recommended.…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…Sheldon et al (12) suggested that pharmacologic agents are likely to be effective in decreasing patient anxiety, though few studies have adequate sample sizes to determine the most effective agents. Both Miyasaka et al (13) and Male et al (14) found that anxiety was reduced after the use of diazepam in one of their anxiety questionnaires but not in all. Helmus et al (15) reported that 10 mg of diazepam had an anxiolytic effect only for highly anxious subjects.…”
mentioning
confidence: 90%